Simplified magnetic resonance index of activity score versus simple endoscopic score in Crohn's disease: prospective study - Nada Saad Mohamed Saad Hassan; Khaled Mohamed Mourad Moghazy; Osama Ebada Salem; Ahmed Hafez Afifi; Doaa Mohamed Emara; Mohamed Masoud Radwan Mohamed (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background To evaluate the correlation between simplified MR index of activity (sMaRIA) score and simple endoscopic score (SES-CD) in Crohn's disease activity assessment. A prospective study was done on established Crohn's disease patients referred to our institution. Magnetic resonance enterography and colonoscopy were performed as an activity assessment protocol searching for activity signs through calculation of sMaRIA score and SES-CD score and correlation between them. One hundred patients were enrolled in the study in period from July 2021 to July 2022. Patients with isolated upper gastrointestinal Crohn's disease (n = 4) or performed surgery before completion of activity assessment protocol (n = 9) or dropout (n = 18) were excluded. Patients with any age group, with ileal or colonic or ileo-colonic Crohn's disease and completed the protocol were eligible for the study (n = 69). Results Sixty-nine patients with 345 bowel segments (five segments for each patient: ileum, right colon, transverse colon, left colon/sigmoid and rectum) were completely evaluated: 33 males and 36 females with mean age 29.16 ± 11.37 years. sMaRIA and SES-CD scores were calculated for each patient (global), and each bowel segment showed 97.50% sensitivity and 79.31% specificity at the level of global scores as well as significant positive correlation between the two scores at patient level/overall segments (rs = 0.816, p < 0.001), at ileal segments (rs = 0.704, p < 0.001) and colonic segments (right colon rs = 0.661, p ≤ 0.001, transverse colon rs = 0.586, p ≤ 0.001, left colon rs = 0.731, p < 0.001 and rectum rs = 0.786, p < 0.001). There were good inter-rater agreement between the two radiologists for the three parameters (wall thickness > 3 mm, mural edema and fat stranding) and moderate for mucosal ulcer detection with k value 0.666, 0.712, 0.712 and 0.565, respectively. Conclusions sMaRIA score is considered to be a reliable tool for Crohn's disease activity evaluation as compared to SES-CD.